Android Based Volleyball Passing Test Instrument Development Design - Destriana Destriana; Destriani Destriani; Ahmad Richard Victorian; Syariah Syariah (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
This study aims to see how the design or design of an android-based volleyball passing test instrument. This study uses the Research and Development (R n d) method using the ADDIE model. The ADDIE model is the Analysis phase, Design phase, Development phase, Implementation phase and Evaluation Phase. This research was carried out on July 17-20 September 2022. This research is only at the design stage, where at this design stage it only displays concepts that are made systematically with the intention of making the product to be developed. The results of this study are where the product is designed using a fitting test tool made with a laser and sensor installed in the test area then Arduino Mega as the brain or input and output controller of a circuit then added with NodeMCU can be used as a data sender so that it can be sent to the application that has been made. and downloaded on an Android-based cellphone, which was created with the help of the internet. Based on this design, it is hoped that it can be continued at the stage of developing an Android-based test instrument. This research is used as the basis for developing an android-based volleyball passing test instrument.